The 1‐min Screening Test for Reading Problems in College Students: Psychometric Properties of the 1‐min TIL. (9th January 2017) - Fernandes, Tânia; Araújo, Susana; Sucena, Ana; Reis, Alexandra; Castro, São Luís
Abstract : Reading is a central cognitive domain, but little research has been devoted to standardized tests for adults. We, thus, examined the psychometric properties of the 1‐min version of Teste de Idade de Leitura (Reading Age Test; 1‐min TIL), the Portuguese version of Lobrot L3 test, in three experiments with college students: typical readers in Experiment 1A and B, dyslexic readers and chronological age controls in Experiment 2. In Experiment 1A, test–retest reliability and convergent validity were evaluated in 185 students. Reliability was >.70, and phonological decoding underpinned 1‐min TIL. In Experiment 1B, internal consistency was assessed by presenting two 45‐s versions of the test to 19 students, and performance in these versions was significantly associated ( r = .78). In Experiment 2, construct validity, criterion validity and clinical utility of 1‐min TIL were investigated. A multiple regression analysis corroborated construct validity; both phonological decoding and listening comprehension were reliable predictors of 1‐min TIL scores. Logistic regression and receiver operating characteristics analyses revealed the high accuracy of this test in distinguishing dyslexic from typical readers. Therefore, the 1‐min TIL, which assesses reading comprehension and potential reading difficulties in college students, has the necessary psychometric properties to become a useful screening instrument in neuropsychological assessment and research. Copyright © 2017 John Wiley & Sons, Ltd.